2018
DOI: 10.1515/jppr-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

Ecological applications of Pseudomonas as a biopesticide to control two-spotted mite Tetranychus urticae: chitinase and HCN production

Abstract: The two-spotted spider mite (Tetranychus urticae Koch) is an important pest of many horticultural crops. A study was conducted to evaluate the effect of three fluorescent Pseudomonas isolates obtained from rhizospheric soil of tomato (Solanum lycopersicon) in Agadir, Morocco: Q110B, Q036B and Q172B, as potential biological control agents for T. urticae. Both acaricide and repellent activities were assessed on homogenous adult mites. The acaricidal activity test evaluated five concentrations of bacterial suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…and Bacillus spp. isolates have mainly been assessed for their acaricidal effects in mortality tests or after being sprayed on the plants [27,28]. Remarkably, all of the above studies have identified several strains of entomopathogens with plant protection capabilities when applied in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…and Bacillus spp. isolates have mainly been assessed for their acaricidal effects in mortality tests or after being sprayed on the plants [27,28]. Remarkably, all of the above studies have identified several strains of entomopathogens with plant protection capabilities when applied in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Several species of Pseudomonas have been shown to bene t plants by alleviating certain stress conditions, and to provide, for example, plant protection [70][71][72]. Members of Pseudomonas have been investigated as biopesticides for control of mites [73,74] and insects [75,76]. Pseudomonas associated with plants that orally infect and kill herbivorous arthropods carry surface glycan decorations to escape the host humoral immune defense [77], killing the hosts by producing molecules with potent insecticidal activity and lytic enzymes (chitinases, phospholipases) (Flury et al 2017;Vacheron et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria can act by several mechanisms in the biocontrol of diseases and pests. The ability to degrade chitin is considered the main mechanism involved in the control of pests [17,18]. Chitinolytic organisms such as Pseudomonas sp.…”
Section: Plos Onementioning
confidence: 99%
“…and Streptomyces sp. isolated from the rhizosphere have been shown to be potential biocontrol agents [16,17,33]. Vodovar et al [15] reported that Pseudomonas entomophila exhibits virulence against D. melanogaster due to strong hemolytic activity involving proteins such as lipases, chitinases and/or hydrolases.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation